Anti‐virulence activity of novel (1‐heteroaryloxy‐2‐hydroxypropyl)‐ phenylpiperazine derivatives against both wild‐type and clinical drug‐resistant Candida albicans strains. Issue 1 (20th November 2022) - Huang, Junjun; Song, Shihao; Zhao, Shuo; Sun, Xiuyun; Wang, Zijie; Huang, Xiaorong; Xiao, Qing; Deng, Yinyue
Abstract: Candida albicans is an important human fungal pathogen. Our previous study disclosed that aryloxy‐phenylpiperazine skeleton was a promising molecule to suppress C. albicans virulence by inhibiting hypha formation and biofilm formation. In order to deeply understand the efficacy and mechanism of action of phenylpiperazine compounds, and obtain new derivatives with excellent activity against C. albicans, hence, we synthesized three series of (1‐heteroaryloxy‐2‐hydroxypropyl)‐phenylpiperazines and evaluated their inhibitory activity against C. albicans both in vitro and in vivo in this study. Compared with previously reported aryloxy‐phenylpiperazines, part of these heteroaryloxy derivatives improved their activities by strongly suppressing hypha formation and biofilm formation in C. albicans SC5314. Especially, (9H‐carbazol‐4‐yl)oxy derivatives 25, 26, 27 and 28 exhibited strong activity in reducing C. albicans virulence in both human cell lines in vitro and mouse infection models in vivo. The compound 27 attenuated the virulence of various clinical C. albicans strains, including clinical drug‐resistant C. albicans strains. Moreover, additive effects of the compound 27 with antifungal drugs against drug‐resistant C. albicans strains were also discussed. Furthermore, the compound 27 significantly improved the composition and richness of the faecal microbiota in mice infected by C. albicans . These findings indicate that these piperazine compounds have great potential to be developed as new therapeutic drugs against C. albicans infection. Abstract : We synthesized a series of new piperazines and tested the piperazine compounds against C. albicans in vitro and in vivo. We screened four effective compounds 25, 26, 27, and 28 for subsequent studies by using cytotoxicity assay. We also found that the compound 27 had a good effect against C. albicans in the mouse systemic infection model and oral infection model. And the compound 27 not only had effect on many clinical C. albicans strains, but also showed synergistic effects with antifungal agents to treat clinical drug‐resistant C. albicans strain. The new compound 27 discovered in this study can provide new direction for developing antifungal agents against C. albicans infection.